Effect of fatigue on force production and force application technique during repeated sprints - Morin, J.-B.; Samozino, P.; Edouard, P.; Tomazin, K. (Journal of Biomechanics, 2011)
We investigated the changes in the technical ability of force application/orientation against the ground vs. the physical capability of total force production after a multiple-set repeated sprints series. Twelve male physical education students familiar with sprint running performed four sets of five 6-s sprints (24 s of passive rest between sprints, 3 min between sets). Sprints were performed from a standing start on an instrumented treadmill, allowing the computation of vertical (FV), net horizontal (FH) and total (FTot) ground reaction forces for each step. Furthermore, the ratio of forces was calculated as RF=FHFTot-1, and the index of force application technique (DRF) representing the decrement in RF with increase in speed was computed as the slope of the linear RF-speed relationship. Changes between pre- (first two sprints) and post-fatigue (last two sprints) were tested using paired t-tests. Performance decreased significantly (e.g. top speed decreased by 15.7±5.4%; P<0.001), and all the mechanical variables tested significantly changed. FH showed the largest decrease, compared to FV and FTot. DRF significantly decreased (P<0.001, effect size=1.20), and the individual magnitudes of change of DRF were significantly more important than those of FTot (19.2±20.9 vs. 5.81±5.76%, respectively; P<0.01). During a multiple-set repeated sprint series, both the total force production capability and the technical ability to apply force effectively against the ground are altered, the latter to a larger extent than the former.